Hobby hackers to billion-dollar industry: the evolution of ransomware. Issue 11 (November 2017) - Srinivasan, CR
Abstract : In recent months, ransomware has become a mainstream topic across the world, thanks to a string of high-profile attacks. There is a sense that no one is immune to attacks from a persistent and organised community of cyber-criminals who use ransomware as their main modus operandi. Ransomware has become a mainstream topic across the world recently, thanks to a string of high-profile attacks. But this form of malware has been with us for a while. Srinivasan CR of Tata Communications examines the history of ransomware, tracing its evolution from crude beginnings in the 1980s to its global impact today. And although it is proving to be a pernicious threat, he explains how we are also developing effective countermeasures.